Predictors of prostate‐specific antigen testing in men aged ≥55 years: A cross‐sectional study based on patient‐reported outcomes. (31st May 2020) - Leong, Joon Yau; Chandrasekar, Thenappan; Berlin, Alejandro; Klaassen, Zachary; Wallis, Christopher JD; Ahmad, Ardalan E; Herrera‐Caceres, Jaime O; Perlis, Nathan; Fleshner, Neil E; Goldberg, Hanan
Abstract : Objectives: To examine the predictors of prostate‐specific antigen discussion with a physician and prostate‐specific antigen testing in men aged ≥55 years. Methods: Utilizing the USA Health Information National Trends Survey, 4th Ed., a cross‐sectional study from 2011 to 2014 was carried out to analyze the factors predicting prostate‐specific antigen testing and discussion in men ≥55 years. Associations between each covariate and prostate‐specific antigen discussion/testing were determined. Multivariable logistic regression models were used to determine clinically relevant predictors of prostate‐specific antigen discussion/testing. Due to multiple comparisons, the Bonferroni correction was used. Results: A total of 2731 men included in the Health Information National Trends Survey were analyzed. Several socioeconomic parameters were found to increase the likelihood of men aged ≥55 years to undergo prostate‐specific antigen testing: living with a spouse, a higher level of education (college graduate or above), a higher income (>$50 000 annually) and previous history of any cancer. In contrast, current smokers were less likely to undergo prostate‐specific antigen testing. Having a prostate‐specific antigen discussion with a physician was more likely for men surveyed in 2014, for men who were living with a spouse, who had a higher annual income (>$50 000 annually) and those with a history of any cancer. Conclusions: Significant inequalities in prostate‐specific antigen testing and discussion exist among men in the USA, mainly driven by socioeconomic factors. Ideally, prostate‐specific antigen testing and discussion should be based on relevant clinical factors with a shared decision‐making approach for every man. Therefore, a better understanding of the socioeconomic factors influencing prostate‐specific antigen testing/discussions can inform strategies to reduce existing gaps in care.